Smart Technologies for Socioeconomic Sustainability in Urban Housing: A Southeast Asian Perspective - Sohaimi, Nor Suzylah; Abd Razak, Muhammad Hafiz; Said, Mohd Syahril; Ibrahim, Filzani Illia; Zıvalı, Tülay (Journal of Contemporary Urban Affairs, 2025)
Rapid urbanisation across Southeast Asia intensifies the demand for housing that is simultaneously affordable, sustainable, and socially inclusive. This study investigates how smart technologies—Artificial Intelligence, Internet of Things devices (IoT), Building Information Modelling, and passive cooling innovations—can advance socioeconomic sustainability in urban housing. A three-phase methodology combined a scientometric analysis of 454 Scopus-indexed papers, a systematic literature review of eight rigorously screened studies, and a qualitative content analysis of practice-based sources. The scientometric mapping reveals growing scholarly attention to energy efficiency and climate resilience, yet affordability and social equity remain peripheral themes. Evidence from Malaysia, Indonesia, the Philippines, Singapore, and Thailand shows that smart sensors, digital simulations, and value-management frameworks can reduce cooling energy by up to 18,000 kWh annually, cut construction costs, and enhance thermal comfort in low-income settings. However, adoption is uneven owing to high capital costs, limited policy incentives, and skills gaps. The study proposes an integrated framework linking environmental performance, housing affordability, and social inclusion through appropriate digital tools. Policymakers and urban planners are urged to embed financing mechanisms, capacity-building, and participatory design into housing programmes to mainstream technology-enabled, equitable sustainability across the region within the next decade.